SISTEM INFORMASI OPERASI DAN PEMELIHARAAN JARINGAN IRIGASI BERBASIS WEBSITE (STUDI KASUS: DAERAH IRIGASI (D.I) WALAHAR, SATUAN PELAYANAN CIWARINGN-SUBA) - Kusdi, Kusdi; Martinus, Agust Isa; Novianti, Dian (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2024)
This research develops a web-based Irrigation Network Operation and Maintenance Information System to make it easier for officers to record records in the Walahar Irrigation Area (D.I), Ciwaringin-Suba Service Unit which still uses conventional methods. The main problem faced is the difficulty of obtaining data on operation and maintenance activities and the length of time for collecting data on the condition of the irrigation network. The developed web-based system helps officers manage daily records and document equipment damage in the field, increasing efficiency and accuracy. In conclusion, switching from conventional to computerized systems provides many advantages, and this system can be further developed to be applied in other irrigation areas. The results of this research can create a website-based information system for the operation and maintenance of irrigation networks that makes it easier for PPA officers, POB, Mantri and Irrigation Staff to record and report without having to wait for forms from the central government. This system can also carry out debit recording calculations according to existing guidelines. Keywords: : Operation and maintenance information systems, operations, maintenanc.